West Bank and Gaza - Investment Climate Assessment : Unlocking the Potential of the Private Sector - World Bank (Washington, DC, 2012)
It is the purpose of this Investment Climate Assessment (ICA) to look at what hinders the move of the Palestinians to new markets and what can be done to encourage it. The ICA reveals that shrinking market access and the lack of free movement are the main constraints to growth for Palestinian enterprises. Relative to other countries in the region, the Palestinian investment climate is good: petty corruption is low, the bureaucracy is relatively efficient and financial markets are well developed. Despite this, Palestinian enterprises have not invested enough to maintain their international competitiveness. However, the report points out that the growing settlements and movement restrictions imposed by Israeli authorities for security reasons overshadow all other elements of the investment climate. The restrictions close off markets, raise transaction costs and prevent producers from guaranteeing delivery dates. The closures also serve to keep firms small and prevent them from attaining minimum efficient scale. The ICA policy recommendations fall into three broad categories: movement and access, the investment climate, and enterprise capabilities. For the Palestinian private sector to fulfill its potential and create the jobs required by the rapidly expanding population, all three of these areas must be addressed. However, re-establishing free movement and access, while maintaining Israeli security, is the sine qua non for a viable Palestinian economy. Without a concerted political effort to re-open markets and lower transaction costs the Palestinian private sector is bound to fail.